OBJECTIVITY ISSUES IN ISLAMIC THOUGHT: A CONCEPTUAL APPROACH - Kourime, Souad (Universitas Islam Negeri Ar-Raniry, 2022)
Objectivity is a key standard to assess any intellectual work in Islamic Thought. This standard helps differentiate between methodological work that is characterized by objectivity, and doctrinal or ideological work where subjectivity predominates. However, there are major obstacles that stand in the way of applying this objective assessment; namely the problem of defining the boundaries between al-Manhajiyah (methodology) and al-Madhhabiyah (doctrinal thinking or ideology) in Islamic Thought. Defining those boundaries encounters, and is influenced by, a series of problems, most notably the conceptual confusion caused by the lack of precision in the definition of the words: al-Manhaj (method) and al-Madhhab (doctrine). This study aims at solving these problems by determining the points of convergence and divergence between what is purely objective and methodological, and what is purely subjective and based on doctrinal affiliation. In order to achieve this goal, this paper used a conceptual approach to study the concepts of al-Manhaj (method) and al-Madhhab (doctrine) based on their maturity, and the agreement upon their meaning. The paper also demonstrated the impact of each criterion on objectivity in Islamic Thought. The methods of research used in this study are thematic and qualitative analysis.